Design Methodology and Beam-Wave Interaction Study of a Second-Harmonic D -Band Gyroklystron Amplifier - Swati M.V.; Chauhan M.S.; Jain P.K. (My University, 2025)
The design methodology of a gyroklystron amplifier has been discussed and subsequently used for the design and optimization of a second-harmonic D -band four-cavity gyroklystron amplifier. The multimode beam-wave interaction behavior of the device operating in the TE02 mode has been analyzed using the time-dependent multimode analysis and also simulated using a commercial 3-D particle-in-cell code 'CST Particle Studio.' The effect of various parameters, such as driver frequency, driver power, beam voltage, and beam current, has been studied to understand its sensitivity on the device performance. The simulation results predict that the designed second-harmonic gyroklystron amplifier produces a stable RF output power of ∼ 1 kW (assuming 0% velocity spread) at 140 GHz center frequency, with ∼ 2.5 % electronic efficiency, ∼ 30 dB gain, and ∼ 1 GHz bandwidth for a 40-kV, 1-A electron beam. © 1973-2012 IEEE.